Human motivation and corporate governance - Tampu, Diana Larisa (Copernican Journal of Finance & Accounting, 2015)
In one stream of research, this paper assesses the effect that human motivation has on Corporate Governance Indicators. By doing this, we will use the six dimensions of corporate governance at country level and four dimensions of human motivation provided by OECD. The human motivation dimensions had been chosen considering the expectations theory of Vroom. The paper is organized into three main parts presenting if the chosen governance indicators have different predictors and different possible consequence that depend on human motivation. The idea that corporate governance should be gain by human motivation will be illustrated from an empirical point of view with data from twenty developed countries from Europe.